Eksistensi Kebijakan Landrente di Karesidenan Madiun Tahun 1811-1870 - Wahyudi, Wahyudi; Miftahuddin, Miftahuddin (Lambung Mangkurat University, 2023)
This study aims to determine the implementation of landrente in the East Indies by Raffles in 1811-1816 and the existence of landrente policies in the Madiun Residency in 1811-1870. This study uses a form of historical research to find out facts and draw conclusions about past events. Sources of data used include primary sources including archives and documents during the implementation period of the landrente and secondary sources include books, articles and interviews related to landrente in the Madiun Residency. Based on the results of the research, it can be concluded that the landrente started since Raffles came to power in 1811-1816 to replace the mandatory submission policy. The existence of land tax in the Madiun Residency still exists in the next period, namely it can change land ownership and land use in the community. From 1811 to 1870, The landrente causes a change in the pattern of land from individual ownership to communal ownership. It also causes changes in land use from agriculture to plantations.